(untitled) (International Journal of Management Trends: Key Concepts and Research, 2024)
This study examines the application of e-learning at the University of Educons, particularly focusing on the adoption of the Moo-dle platform and the development of a proprietary platform in response to the increased demand for online education during the COVID-19 pandemic. The research analyzes the effectiveness of these platforms in achieving the university's strategic goals, including enhancing staff training, providing access to modern scientific trends, introducing a transparent distance education system, and improving the overall quality of education. The study explores student perceptions and experiences with online learning, highlighting the positive reactions and the platforms' seamless integration into the teaching process. Furthermore, the research discusses the benefits of e-learning in terms of cost savings, flexibility, and accessibility for students who may not be able to participate in traditional classroom settings. The findings contribute to a broader understanding of the role and impact of e-learning in higher education, particularly in adapting to unforeseen circumstances and evolving educational needs. The study concludes by emphasizing the long-term potential of e-learning as a valuable investment for educational institutions and students alike.